Iran's rocket and missile forces and strategic options a report of the CSIS Burke Chair in Strategy - Cordesman, Anthony H. (Center for Strategic and International Studies Rowman & Littlefield, 2014)
Iran's rocket and missile forces serve a wide range of Iranian strategic objectives. These forces range from relatively short-range artillery rockets that support its ground forces and limit the need for close air support to long-range missiles that can reach any target in the region and the development of booster systems that might give Iran the ability to strike at targets throughout Europe and even in the United States. Iran's forces and systems are steadily evolving. While the lethality of most current systems is limited by a reliance on conventional warheads, poor accuracy, and uncertain reliability, Iran is developing steadily improved guidance systems, attempting to improve the lethality of its conventional warheads, and has at least studied arming its missiles with nuclear warheads.